Preoperative multidisciplinary team assessment is associated with improved survival in patients with locally advanced colon cancer; a nationwide cohort study in 3157 patients. Issue 9 (September 2021) - Rosander, E.; Holm, T.; Sjövall, A.; Hjern, F.; Weibull, C.E.; Nordenvall, C.
Abstract: Introduction: Multidisciplinary team (MDT) assessment is associated with improved survival in locally advanced rectal cancer, but the effect of an MDT assessment on survival in locally advanced colon cancer has not been reported. The aim of this national population-based cohort study was to establish if preoperative MDT assessment affects prognosis in patients with primary locally advanced colon cancer. Material and methods: All patients in Sweden with locally advanced colon cancer, without metastatic disease, who underwent an elective colon resection between 2010 and 2017 were identified through the Swedish Colorectal Cancer Registry (SCRCR), and the cohort was linked to national registers. Data on patient characteristics, preoperative staging, surgical procedures, recurrence and survival were collected from SCRCR. The association between MDT assessment and colon cancer-specific survival was evaluated using Kaplan-Meier survival curves and Cox proportional hazards models. The multivariable analysis was adjusted for sex, age, ASA grade, CCI, time period, pN, region and preoperative MDT. Results: MDT assessment was performed in 2663 patients (84.4%) of 3157 eligible patients. The 3-year colon cancer-specific survival was higher following MDT, compared with no MDT assessment (80% versus 68%). MDT assessment was independently associated with reduced colon cancer-specific mortality (HR 0.70, 0.57–0.84 95% CI). Conclusion: Preoperative MDT assessment is associated with an improved long-term survival in patients with locally advanced colon cancer and should be mandatory in patients with suspected locally advanced colon cancer.